Analisis Gaya Kepemimpinan Dan Budaya Kerja Perusahaan Terhadap Kepuasan Karyawan (Studi Kasus PT Flexylabs Instrument Indonesia) - Juniar, Sonya Amelia; Yoganingsih, Tutiek (CV. ITTC INDONESIA, 2024)
This study aims to determine how the relationship between the variables of Leadership Style (X1), Work Culture (X2), on the variable Employee Satisfaction (Y) at PT Flexylabs Instrument Indonesia. The research data is data taken using a questionnaire distributed to employees of PT Flexylabs Instrument Indonesia. The population in this study were 40 employees of PT Flexylabs Instrument Indonesia, where in determining the sample using simple random sampling, resulting in a sample of 40 employees with SEM-PLS analysis techniques using SmartPLS4 software to process data in this study. The findings of the research that has been done show that: 1) Leadership style has a positive and significant effect on employee satisfaction. 2) Work Culture has a positive and significant effect on Employee Satisfaction. 3) Leadership Style and Work Culture have a positive but insignificant effect on Employee Satisfaction.